1991
DOI: 10.1177/089686089101100204
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Selection-Adjusted Comparison of Patient and Technique Survivals on CAPD and Hemodialysis

Abstract: Four hundred and eighty CAPD and 373 HD patients started regular dialysis treatment between 1981 and 1987 in 6 dialysis centers. The CAPD patients were 6 years older, on average, than the HD patients and had more complicating conditions (43.3% with 3 or more coexisting risk factors versus 28.9% with coexisting complications). The 7-year patient survival rate was not significantly different. Cox's proportional hazards regression showed that age, cardiovascular disease, cerebrovasculardisease, peripheral vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(73 citation statements)
references
References 15 publications
5
66
1
1
Order By: Relevance
“…Although the rates of peritonitis have decreased significantly in recent years, the outcome of patients with peritonitis has not significantly improved despite the technical advances. [1][2][3] Peritoneal biopsies obtained from dialyzed patients show that the architecture of the peritoneum is severely damaged during peritonitis. 4 In addition, several lines of evidence, obtained from both patients with peritonitis and animal models, have shown that acute peritonitis is characterized by increased transport of small solutes and glucose as well as loss of protein and ultrafiltration.…”
mentioning
confidence: 99%
“…Although the rates of peritonitis have decreased significantly in recent years, the outcome of patients with peritonitis has not significantly improved despite the technical advances. [1][2][3] Peritoneal biopsies obtained from dialyzed patients show that the architecture of the peritoneum is severely damaged during peritonitis. 4 In addition, several lines of evidence, obtained from both patients with peritonitis and animal models, have shown that acute peritonitis is characterized by increased transport of small solutes and glucose as well as loss of protein and ultrafiltration.…”
mentioning
confidence: 99%
“…11 Yet, it has been reported that CAPD patients have higher adjusted mortality risk and more atherosclerotic changes than HD patients. 12,13 The majority of studies on the prevalence and importance of periodontal disease and related factors have focused on HD patients, 4,7,14 and data regarding CAPD patients are scarce. 15 Furthermore, a study by D'Aiuto et al 16 suggested that control of local periodontal infections was associated with a decrease in the levels of serum inflammatory markers.…”
mentioning
confidence: 99%
“…In a multicenter cohort study in England, a prior history of cardiovascular/cerebrovascular disease was an even stronger predictor of patient survival than age and diabetes (1 5). The multicenter study from Italy demonstrated the adverse effect of age and a variety of co-morbid factors (28). The studies from England ( 15) and Italy (28) identified no risk factor associated with transfer from CAPD to hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Maiorca et al (28) reported the results of a six-center study in Italy that compared, after selection adjustment, the patient and technique survivals for patients starting treatment with hemodialysis and CAPD between 198 1 and 1987. While there were no differences detected between treatment modalities, the Cox proportional hazards regression model (25) revealed a significantly worse survival for age greater than 53.5 years, diabetes, malignancy, peripheral vascular disease, cerebrovascular disease, ischemic cardiomyopathy, and multisystem disease.…”
Section: Baseline Prognostic Factors and Clinical Outcomementioning
confidence: 99%